2016
DOI: 10.1186/s40886-016-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of research evidence in clinical practice to improve health care delivery- practices, attitudes and challenges faced by physiotherapists in Zimbabwe: a descriptive cross sectional study

Abstract: Background: Decision-making in health care delivery should be based on the best available current, valid and relevant evidence. Healthcare professionals should therefore be well versed with the skills required to make evidence based clinical decisions in patient care. The aims of this study were to investigate the attitudes of physiotherapists towards utilisation of evidence-based practice (EBP) during patient care, identify barriers to the use of EBP and strategies to improve utilisation of EBP. Method: A des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This implies that, with the removal of the barriers or with some type of facilitation process, they would be willing to employ EBP at a higher level. This finding is also supported by systematic reviews which found insufficient time to be the most important barrier (Scurlock-Evans et al 2014 ; Tadyanemhandu et al 2016 ). Other studies also established that the respondents believed that insufficient time was the most important barrier: Salbach et al ( 2007 ) at 52%; Akinbo et al ( 2008 ) at 64%; Nilsagård and Lohse ( 2010 ) at 86%; Heiwe et al ( 2011 ) at 43.5% and Ramírez-Vélez et al ( 2015a ) at 84%.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This implies that, with the removal of the barriers or with some type of facilitation process, they would be willing to employ EBP at a higher level. This finding is also supported by systematic reviews which found insufficient time to be the most important barrier (Scurlock-Evans et al 2014 ; Tadyanemhandu et al 2016 ). Other studies also established that the respondents believed that insufficient time was the most important barrier: Salbach et al ( 2007 ) at 52%; Akinbo et al ( 2008 ) at 64%; Nilsagård and Lohse ( 2010 ) at 86%; Heiwe et al ( 2011 ) at 43.5% and Ramírez-Vélez et al ( 2015a ) at 84%.…”
Section: Discussionmentioning
confidence: 59%
“…Positive attitudes were also identified by Scurlock-Evans et al (2014) in a systematic review, as well as in other studies which found physiotherapists with positive attitudes and perceptions regarding EBP (Frantz & Diener 2009;Hannes et al 2009;Heiwe et al 2011;Iles & Davidson 2006;Jette et al 2003;Ramírez-Vélez et al 2015b;Schreiber et al 2009;Silva et al 2015;Tadyanemhandu et al 2016;Yahui & Swaminathan 2017). Specifically, the respondents were found to have a positive attitude to the fact that 'evidence-based practice is important for offering patients the best possible treatment'; and that 'it is important that evidence-based guidelines related to their work exist'.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…An understanding of professional roles within teams can be acquired through interprofessional collaboration during undergraduate education (Berman, 2013). Practicing clinicians may be educated by means of courses, workshops, team meetings, grand rounds and research publications (Tadyanemhandu et al, 2016). In collaboration with other rehabilitation professions, physiotherapists should imprint their hallmark in primary HIV care (Cobbing et al, 2013).…”
Section: Health Care Financementioning
confidence: 99%